Politeness Strategies Used by Tom Cotton to Ask Questions in Congress Interviews: A Comparative Analysis - Mutiara Mutiara; Affifah Syahlina Br. Hutagalung; Thesia Aprianti Purba; Elizabeth Rusida Yosephine Br. Tamba (English Literature Study Program, Faculty of Humanities, Diponegoro University, 2025)
This research aims to examine the politeness strategies used by Tom Cotton to ask questions in congress interviews. This research uses a qualitative descriptive method by collecting the data from his two congress interview videos with the TikTok CEO, Shou Zi Chew, and the Secretary of the Army, Christine E. Wormuth, on YouTube. The data are in the form of phrases and clauses that contained politeness strategies. In analyzing the data, the researchers compare the data using the theories of politeness strategy by Brown and Levinson (1987) to outlines the different types of politeness strategy such as: bald on record, positive politeness, and negative politeness, that Cotton used in the interviews. The data is never analyzed yet by any researcher before. After analyzing the data, the researchers found three types of politeness strategies in the Tom Cotton’s question interviews at congress: Bald on record, positive politeness, and negative politeness, and also found the differences and similarities of the way of Tom Cotton’s interviews.